Filsafat Pendidikan Islam Sebagai Pondasi Pendidikan Karakter dalam Membangun Generasi Unggul - sitisarohhasibuan; Dena Aulia Harani; Rusdiah Roitona Nasution; Herlini Puspika Sari (MGMP PAI SMP BINTAN, 2025)
This study aims to analyze the philosophy of Islamic education as the main foundation in the formation of character education to build a superior generation that is faithful, knowledgeable, and has noble morals. This study focuses on the weak implementation of the values ​​of Islamic educational philosophy in the character formation of the younger generation amidst moral degradation and the challenges of globalization. The study used a library research method by reviewing various literature sources such as books, scientific journals, and relevant academic articles. The results show that the philosophy of Islamic education, which is based on the values ​​of monotheism, noble morals, knowledge, and wisdom, plays a significant role in shaping the perfect human being through a balance of spiritual, moral, intellectual, and social aspects. Its implementation is proven effective when integrated into the curriculum, learning methods, teacher role models, and the habituation of Islamic values ​​in the educational environment.